Social media and academic performance of secondary school students in Enugu East Local Government Area, Enugu State, Nigeria. - Aniagolu, Hyacinth N. (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
Social media has become the world’s fastest means of communication. It provides a variety of information to consumers such that hardly a day passes without recourse to social media by both the young and the old alike. However, the uncontrolled use of social media by young people in secondary school seems to have a devastating effect on their academics. This study therefore investigated the use of social media and its implication on the academic performance of secondary school students in Enugu East Local Government Area. The study was guided by three research questions and the corresponding research objectives. It was a cross-sectional survey. The population of the study was 13605 from which a sample size of 400 students was generated using the Taro Yameni formula for sample size determination. Data was analysed using mean. It was found that the use of social media affects the class participation of government secondary school students in Enugu East Local Government Area. It was equally found that the use of social media affects the study habits of government secondary school students. It was also found that the use of social media affects the behavioural patterns of government secondary school students. It was recommended that schools place an outright ban on the use of gadgets that distract students while in school, particularly those in secondary schools. Again, the Government should be stricter on the laws prohibiting the underaged from having subscriber identification modules (SIM cards) and or e-mail addresses. More so, teachers should be very watchful of the students while in the class to identify students using cell phones. This would reduce the problems of distractions that emanate from the use of social media.